Evaluation of prime boosting vaccination strategy using newly constructed tuberculosis vaccine candidates in mice - Zakaria, Nurazwana (2013)
Tuberculosis (TB) an infectious disease caused by Mycobacterium tuberculosis complex continues to be major health problem, worldwide. Current the only available preventive TB vaccine used is Bacillus Calmette Guerin (BCG) but unfortunately, the efficacy of BCG nowdays is controversial. Different vaccine delivery approaches have been developed based on the available technologies. In this study, we are using two previously constructed vaccine candidates namely VacIV DNA vaccine and StVacIII surface display vaccine, together with standard BCG vaccine employing prime boosting vaccination strategy. VacIV DNA vaccine was given intramuscularly to mice while StVacIII surface display vaccine and BCG was given orally. Mice whole blood and splenocytes from the vaccinated mice were tested for various immunological tests. The results showed that mice whole blood (peripheral blood) and splenocytes from the immunized mice were found to increase the production of IL-2 and IFN-y when stimulated with the antigen (Mtb 8.4) which is one of the epitopes in both VacIV and VacIII DNA vaccine. Flow cytometric intracellular cytokine analysis of splenocytes from vaccinated mice showed that both CD4+ and CD8+ T cells produce IL-2 and IFN-y upon stimulation with the antigens. The same responses also were seen in peripheral blood. In the prime-boost approach, the study showed that mice primed using StVacIII surface display vaccine and boosted with VacIV DNA vaccine is a better strategy in increasing the immune response in mice. In conclusion, the data obtained from this study suggested that surface display vaccine in combination with DNA vaccine using prime-boost vaccination strategy gives new ideas in vaccine development against tuberculosis. Further study is required to confirm the efficacy of the prime-boosting vaccination strategy in term of protection in animal model.